Tap dancers in the wild: field observations of multimodal courtship displays in socially monogamous songbirds - Ota, Nao (Naturwissenschaften, 2020)
Multimodal signaling systems are shaped not only by a signaler’s physical abilities but also by external factors such as the position of signal receivers and the properties of the medium through which the signals are transmitted. To fully understand the evolution and function of multimodal communication, it is essential to investigate the behavior in the wild. Here, I present evidence that socially monogamous songbirds perform complex courtship displays that can produce multimodal and multicomponent signals in wild conditions. Cordon-bleus (Uraeginthus spp.) are socially monogamous songbirds from East Africa. Both sexes of cordon-bleus perform multimodal courtship displays by holding a piece of nest material, bobbing up and down, and singing. My previous laboratory study using high-speed video cameras revealed that courtship bobbing includes multiple rapid steps similar to human tap-dancing, which presumably contributes to producing non-vocal sounds and/or vibrations in addition to visual signals. As a result of field observation and behavioral analysis, I found that wild cordon-bleus perform tap-dance like displays just as captive cordon-bleus. I also observed that wild cordon-bleus produced non-vocal sounds and shook branches during courtship, which can contribute to multimodal signal production (i.e., visual, acoustic, and vibrational signals). My findings imply that the courtship displays of cordon-bleus are an ideal candidate for investigating the role and function of multimodal communication in animals, and demonstrate the importance of further quantitative studies in both laboratory and field. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00114-020-01686-x) contains supplementary material, which is available to authorized users.